Предмет: Математика,
автор: Аноним
6⋅x−(x+10) при x = −6.
Ответы
Автор ответа:
0
Ответ:
-40
Пошаговое объяснение:
6×(-6)-(-6+10)
-36-4
Аноним:
Хотя здесь легкие числа, все равно надо выражение сначала упростить, а потом подставлять))
Автор ответа:
0
Сначала упростим
6х-х-10=5х-10
при х=-6
5х-10=5*(-6)-10=-30-10=-40.
Похожие вопросы
Предмет: Геометрия,
автор: Ffffgп
Предмет: Математика,
автор: FBiy
Предмет: Химия,
автор: fqc
Предмет: История,
автор: bes505
Предмет: Информатика,
автор: Zharkovauliya